Implementasi Kebijakan Penanggulangan Bencana Daerah di Kota Sukabumi - Nabila Rahma Silmi; Tuah Nur; Dian Purwanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this research is to find out the implementation of regional disaster management policies in Sukabumi City and to find out the inhibiting and supporting factors of the successful implementation of regional disaster management policies. This research method uses descriptive analysis method with a qualitative approach. The results showed that the implementation of regional disaster management policies was not optimal. The conclusion is that the socialization activities are still lacking and equitable, human resources and infrastructure have not been added yet. The inhibiting factors are in terms of institutional, apparatus discipline, budget, resources, facilities and environment that are less conducive. Supporting factors are the existence of regulations or regulations on disaster management. for communication carried out by BPBD Sukabumi City in carrying out socialization activities or training on disaster management to the public is still lacking and uneven. Keywords: Implementation, Policy, Disaster Management.